Interest in using mobile technology to help self-manage alcohol use among persons living with the human immunodeficiency virus: A Florida Cohort cross-sectional study. Issue 1 (2nd January 2018) - Sharpe, J. Danielle; Zhou, Zhi; Escobar-Viera, César G.; Morano, Jamie P.; Lucero, Robert J.; Ibañez, Gladys E.; Hart, Mark; Cook, Christa L.; Cook, Robert L.
ABSTRACT: Background: Alcohol consumption at hazardous levels is more prevalent and associated with poor health outcomes among persons living with the human immunodeficiency virus (HIV; PLWH). Although PLWH are receptive to using technology to manage health issues, it is unknown whether a cell phone app to self-manage alcohol use would be acceptable among PLWH who drink. The objectives of this study were to determine factors associated with interest in an app to self-manage drinking and to identify differences in baseline mobile technology use among PLWH by drinking level. Methods: The study population included 757 PLWH recruited from 2014 to 2016 into the Florida Cohort, an ongoing cohort study investigating the utilization of health services and HIV care outcomes among PLWH. Participants completed a questionnaire examining demographics, substance use, mobile technology use, and other health behaviors. Multivariable logistic regression was used to identify factors significantly associated with interest in an app to self-manage drinking. We also determined whether mobile technology use varied by drinking level. Results: Of the sample, 40% of persons who drink at hazardous levels, 34% of persons who drink at nonhazardous levels, and 19% of persons who do not drink were interested in a self-management app for alcohol use. Multivariable logistic regression analysis indicated that nonhazardous drinking (adjusted odds ratio [AOR] = 1.78; confidence interval [CI 95%]: 1.10–2.88) and hazardous drinking (AOR = 2.58; CI: 1.60–4.16) were associated with interest, controlling for age, gender, education, and drug use. Regarding mobile technology use, most of the sample reported smartphone ownership (56%), text messaging (89%), and at least one cell phone app (69%). Conclusions: Regardless of drinking level, overall mobile technology use among PLWH was moderate, whereas PLWH who consumed alcohol expressed greater interest in a cell phone app to self-manage alcohol use. This indicates that many PLWH who drink would be interested in and prepared for a mobile technology–based intervention to reduce alcohol consumption.